PEMBUATAN DAN KARAKTERISASI SULFONAT TERIMPREGNASI PADA SILIKA DARI ABU SEKAM PADI (RICE HUSK ASH) - Nirwanto Pasuluran; Erwin Erwin; Noor Hindryawati (PROSIDING SEMINAR KIMIA, 2017)
Preparation of sulfonate silica as acid catalyshas been done with rice husk ash material using impregnation method. The process of making the catalyst was conducted on the extraction and impregnation. The results of the study were characterized using FT-IR spectrophotometer and SEM. Based on the FT-IR resultsthere is vibration from the group S=O at a wavelength of 1069.73 cm-1 is and pores on the surface of the silica filled by molecules of –SO3H Keywords: Silica,Rice Husk Ash, Impregnation